Study guides

☆☆

Q: 9b plus 7 equals 19 plus 3b?

Write your answer...

Submit

Related questions

3A + 9B = 3(A + 3B)

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

Since 3b is a factor of 9b, it is automatically the GCF.

You would factor 3a + 9b as: 3(a+3b)

3b+6b=9b

It is not an equation but an algebraic expression that can be simplified to: 12b-5a

b= 10

9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)

If you mean: (3b+7)^2 then it is 9b^2+42b+49

The simplified expression is -9a -9b.

Gh

There are 3 terms in the given expression of 6a+9b+15

10b

-28am + 17b

2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4

15b+2-13 = 13b+6-4b 15b-11 = 9b+6 15b-9b = 6+11 6b = 17 b =17/6 or 2 and 5/6

3a + 5b - 6a - 9b = -3a - 4b

9b-13b= -4b -4b = 40 Divide both sides by -4 b = -10

All the terms in b add to 11, so 11b = 132 making b = 12

-7a-7b

4a+2b-1a+9b combine all alike variables using commutative property of addition 4a-1a+2b+9b Then add the like variables 3a+11b

(27a)2 = 729a2 (9b)3 = 729b3 So (27a)2 + (9b)3 = 729*(a2 + b3)

There are three terms in the given expression.

When simplified it is: 2a+8b+4

The question is ambiguous because there is no sign shown before the final 6. Assume it is +6 since -6 would make factorisation very difficult. Thus the equation is 6b2 - 13b + 6 = 0 Then 6b2 - 4b - 9b + 6 = 0 or 2b(3b - 2) - 3(3b - 2) = 0 ie (3b - 2)(2b - 3) = 0 then 3b -2 = 0 or 2b - 3 = 0 so 3b =2 or 2b = 3 ie b = 2/3 or b = 3/2